Adolescents’ ultra-processed food consumption status and its association with food literacy: a cross-sectional study in Chongqing, China - Guo, Jiaxin; Shi, Ya; Su, Yu; Jiang, Ke; Luo, Yaocheng; Zhang, Huiyi; Li, Shengping; Shi, Zumin; Ran, Liang; Zhao, Yong (Frontiers in Nutrition, 2025)
BackgroundThe consumption of ultra-processed foods (UPFs) is increasing globally and has become a prominent public health concern. We aimed to use a population-based study to examine the association between food literacy (FL) and its two subdomains with UPF consumption in adolescents.MethodsThe online survey included 7,761 adolescents aged 11–17 from Chongqing, China. UPF consumption degree was assessed by the unhealthy eating subscale of the Healthy and Unhealthy Eating Behaviors Scale (HUEBS). FL was measured using the Food Nutrition Literacy in School-age Children (FNLQ-SC) questionnaire. FL and the two subdomains were categorized into quartiles, and linear regression was used to examine the association between them.ResultsIn fully adjusted regression models, the regression coefficients β (95% confidence interval) were 0.00, −0.68 (95% CI: −1.12, −0.24; p = 0.003), −0.69 (95% CI: −1.14, −0.24; p = 0.003), and −0.60 (95% CI: −1.06, −0.14; p = 0.012) across the FL quartiles. An inverse association between FL and UPF consumption score was observed only in girls, but not in boys. Among those with screen time ≥2 h/day, participants in the higher quartile of FL scores (Q3) exhibited lower scores in UPF consumption compared with those in quartile 1 (Q1) (β (95% CI) −1.35 (−2.00, −0.71), p < 0.05). There were significant interactions between FL quartiles and gender (p for interaction < 0.001) or screen time (p for interaction = 0.003) in relation to UPF consumption.ConclusionThis study suggests that high FL and the two subdomains were linked with a lower UPF consumption score in adolescents. Increasing FL among adolescents has the potential to enhance their decision-making on eating.